THE DEVELOPMENT OF A BILINGUAL BOOK BASED ON THE HISTORY OF NAGA AT WAT SRIDARAM, UDON THANI TO PROMOTE TOURISM - Thongsombat, Kittipong; Chatdecha, Chanika (วารสารนิสิตวัง, 2026)
The study aimed to 1) explore the historical and mythological narratives of the Naga at Wat Sridaram, 2) develop a bilingual book from the adapted narratives, and 3) investigate the satisfaction of the target audience with the content, language, and presentation of the bilingual book about the Naga at Wat Sridaram. Borg and Gall’s (1989) Research and Development (R and D) framework and a mixed-method design of both integrating qualitative and quantitative approaches were employed. Semi-structured interviews were conducted with monks, community members, business owners, tourists, and local officers to collect information. The prototype was evaluated through expert reviews and satisfaction surveys with 35 target readers. Data were analyzed using mean and standard deviation. The findings showed that: 1) Expert reviews indicated a highest level of overall satisfaction of the bilingual book (Mean = 4.26, SD = 0.62), with design receiving the highest rating (Mean = 4.60, SD = 0.58). 2) The satisfaction survey likewise reflected a highest level of overall satisfaction score of the bilingual book (Mean = 4.29, SD = 0.85) with the design achieving the top-rated aspect (Mean = 4.38, SD = 0.88). These findings indicate that the bilingual book demonstrates high quality and effectiveness and is suitable for publication and practical use in cultural tourism promotion.